European Minimum Standards for Obstetric Analgesia and Anaesthesia Departments: An Experts' Consensus. Issue 3 (25th September 2021) - Guasch, E.; Brogly, N.; Mercier, F.J.; Ioscovich, A.; Weiniger, C.F.; Lucas, N.; Chassard, D.; Kranke, P.; Whitaker, D.; Geldner, G.; Sabelnikovs, O.; de Robertis, E.
Abstract : ( Eur J Anaesthesiol . 2020;37:1115–1125) Currently, no minimum standards of anesthesia care for obstetric patients have been defined in Europe or the European Union. Moreover, obstetric anesthesia standards vary widely within and between countries. Providing recommendations for obstetric anesthesia care helps improve maternal safety and quality care across Europe.